LECTORA INSPIRE AS MEDIA IN DELIVERING TEFL MATERIALS FOR ENGLISH DEPARTMENT OF UNISKA (RETAIN, 2016)
LECTORA INSPIRE AS MEDIA IN DELIVERING TEFL MATERIALS FOR ENGLISH DEPARTMENT OF UNISKA Dita Nanda Rosevella English Department, Languages and Arts Faculty, The State University of Surabaya Email:ditarosevella@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Department, Languages and Arts Faculty, The State University of Surabaya Email:pungki_unesa@yahoo.co.id Abstract In this study, researcher observed the use of Lectora Inspire as media in delivering TEFL materials for English Department of UNISKA. The researcher used descriptive qualitative research design by observing the implementation of Lectora Inspire as media in delivering TEFL materials, students’ speaking ability results, and students’ responses. The researcher observed the lecturer and the students activitiesinTEFL class A on English Department of UNISKA. In the teaching lerning process, not only the lecturer who presents TEFL materials by using Lectora Inspire, but also the students given opportunities to present TEFL materials using Lectora Inspire with the intention to make the presentation more interesting. Almost all of the students can operate Lectora Inspire well, only a few of them which had idea that operating Lectora Inspire is little bit difficult. Lectora Inspire gave positive contribution for both of the lecturer and the students in teaching-learning activity. All of them stated that Lectora Inspire which is used as media in teaching the students made them more motivated in learning TEFL or English. It is because of the various features which have been provided by Lectora Inspire. The lecturer or the students can add video, animation, or test through this e-learning. Keywords : : Lectora Inspire,Teaching Media, Audio-Visual Aids, TEFL Abstrak Pada penelitian ini, peneliti mengamati penggunaan Lectora Inspire sebagai media untuk penyampaian bahan pembelajaran TEFL untuk mahasiswa English Department di Universitas Islam Kadiri. Peneliti menggunakan metode deskriptif kualitatif dengan cara mengamati implementasi dari Lectora Inspire sebagai media dalam menyampaikan materi TEFL, hasil dari kemampuan berbicara mahasiswa, dan respon mahasiswa. Peneliti mengamati aktivitas dosen dan mahasiswa di kelas TEFL A di Departemen Bahasa Inggris Universitas Islam Kadiri. Pada proses belajar mengajar, tidak hanya dosen yang menyampaikan meteri TEFL menggunakan Lectora Inspire, tetapi mahasiswa juga diberikan kesempatan untuk menyampaikan materi TEFL menggunakan Lectora Inspire dengan tujuan untuk membuat presentasi lebih menarik. Hamper semua mahasiswa dapat mengoperasikan Lectora Inspire dengan baik, hanya sedikit dari mereka yang merasa sedikit kesulitan dalam mengoperasikan Lectora Inspire. Lectora Inspire member kontribusi yang positif untuk dosen dan mahasiswa dalam proses belajar mengajar. Mereka berpendapat bahwa Lectora Inspire yang digunakan sebagai media dalam mengajar mahasiswa membuat mereka semakin termotivasi dalam belajar TEFL atau Bahasa Inggris. Hal ini dikarenakan bermacam-macam fitur yang telah disediakan oleh Lectora Inspire. Dosen dan mahasiswa dapat menambahkan video, animasi, atau tes menggunakan e-learning ini. Kata Kunci: Lectora Inspire, Media Pembelajaran, Media Pembelajaran Audio-Visual, TEFL